Bupivacaine-Fentanyl Induced Anaphylactic Reaction in Cesarean Delivery Undergoing Spinal Anesthesia: A Case Report - Ulfa Filliana; Firda Ridhayani; Dwi Pura Bagas Towo; Amalia Nurul Ulum (RSUP Dr. Kariadi, 2025)
BACKGROUND: Incidences of anaphylaxis during pregnancy are unreported but high risks to both infant and mother due to pharmacokinetic profile changes of local anesthesia agents in pregnancy. CASE: A 36-year-old woman (G4P2A1) delivered an infant at 40 weeks of her gestation using a cesarean surgical procedure with spinal anesthesia technique. The spinal anesthetic was administrated bupivacaine 15 mg and adjuvant analgesic (fentanyl 25 mcg). The delivery proceeded seamlessly. The patient was experiencing itching, swelling, and erythema in almost every part of her body, including her face, neck, arm, thigh, and leg in 43 minutes after drugs administration. This anaphylaxis reaction resolved after 22 minutes using 2 ampoules of intravenous dexamethasone 5 mg/ml and 1 ampoule of intravenous methylprednisolone 125 mg/ml. No data on second phase allergy was reported from the patient and infant who are born healthy and have a good response, indicated by an Apgar score 8-9. CONCLUSION: The alterations pharmacokinetic profile of local anaesthesia in pregnancy can cause adverse effects such as anaphylaxis reactions. Anaphylaxis reactions require suitable therapeutic intervention (adrenaline and glucocorticoids) to ensure the safety of both the mother and infant during the delivery operation.